Hsp90 up-regulates PD-L1 to promote HPV-positive cervical cancer via HER2/PI3K/AKT pathway - Jie Zeng; Si-Li He; Li-Jie Li; Chen Wang (BMC, 2021)
Abstract Background HPV16 is the predominant cancer-causing strain that is responsible for over 50% of all cervical cancers. In this study, we aim to investigate the therapeutic effect of heat shock protein 90 (Hsp90) knockdown on HPV16+ cervical cancer progression and the underlying mechanism. Methods The transcript and protein expression of Hsp90 in normal cervical and HPV16+ cervical cancer tissues and cell lines were detected by qRT-PCR, immunohistochemistry staining and Western blot. Hsp90 knockdown clones were established using HPV16+ cervical cancer cell line Caski and SiHa cells. The effect of Hsp90 knockdown on HER2/PI3K/AKT pathway and PD-L1 expression was characterized using qRT-PCR and Western blot analysis. Cell proliferation and migration were determined using MTT and transwell assays. Using mouse xenograft tumor model, the impact of Hsp90 knockdown and PD-L1 overexpression on tumor progression was evaluated. Results Hsp90 expression was up-regulated in HPV16+ cervical cancer tissues and cells. Knockdown of Hsp90 inhibited proliferation and migration of Caski and SiHa cells. PD-L1 expression in cervical cancer tissues was positively correlated with Hsp90 expression, and Hsp90 regulated PD-L1 expression via HER2/PI3K/AKT signaling pathway. The results of mouse xenograft tumor model demonstrated Hsp90 knockdown suppressed tumor formation and overexpression of PD-L1 simultaneously eliminated the cancer-suppressive effect of Hsp90 knockdown. Conclusion In this study, we demonstrated a promising tumor-suppressive effect of Hsp90 knockdown in HPV16+ cervical cancers, and investigated the underlying molecular pathway. Our results suggested that Hsp90 knockdown holds great therapeutic potential in treating HPV16+ cervical cancers.